Nutrition Transition in Morocco - Allali, Fadoua (Integrative Journal of Medical Sciences, 2017)
Morocco is undergoing a food transition that affects the urban and rural environment. Urbanization, economic development, and globalization are at the origin of changes in nutritional habits. The Moroccan diet, “Mediterranean type”, is based on a large consumption of cereals and fruits, and vegetables. Food is gradually diversifying, especially for urban households and the wealthier classes. It includes more foods rich in micronutrients, but the consumption of animal-origin products remains very limited whereas the resources of the country, particularly in fish, are very important. Fast food becomes more prevalent in urban areas, encouraging the consumption of foods rich in sugar and fat. This evolution reflects the ongoing nutritional transition in rural as well as urban areas. Coupled with a reduction in physical activity, these changes lead to the progression of overweight and obesity in the adult population